Increasing Students’ Mastery in Tense by Using DOTEN Media - Syahraini, Intan Fitrah; Afrida, Nina; Afna, Mauloeddin (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2024)
This Classroom Action Research (CAR) investigated the effectiveness of Domino Tenses Learning Media (DOTEN) in enhancing students' mastery of the simple present tense in English. The study involved 25 seventh graders (15 females, 10 male) from class VII.A at SMPN 1 Langsa, Indonesia. A two-cycle CAR design was employed, with each cycle consisting of two meetings. Data collection methods included observation, document analysis, and pre- and post-tests. Jean McNiff's CAR framework guided the research process, encompassing planning, implementation, observation, and reflection. The findings demonstrated a significant improvement in students' understanding and application of the simple present tense after utilizing DOTEN media. The minimum mastery criterion (KKM) for this study was set at 72. The average score in cycle I was 50.96, rising to 73.3 in cycle II. This increase suggested that DOTEN media effectively facilitated learning. Additionally, observations revealed a positive shift in student attitudes towards learning the simple present tense. Students displayed increased engagement, characterized by smiles, laughter, and active participation during DOTEN activities. These observations suggested that the game-based nature of DOTEN media fostered enjoyment and motivation, ultimately contributing to improved learning outcomes. In conclusion, this study provided evidence that DOTEN media is valuable tool for enhancing students' mastery of the simple present tense. The research findings offered valuable insights for English language educators seeking to integrate engaging and effective instructional strategies into their classrooms.